2006
DOI: 10.1590/s0102-05362006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Produção hidropônica de alface em solução nutritiva com e sem silício

Abstract: O cultivo hidropônico de plantas noBrasil tem crescido nos últimos anos. No entanto, a sua técnica é pouco conhecida por parte dos agricultores tradicionais, o que gera apreensão e insegurança em adotar este sistema de produção. Porém, buscando atender a um mercado cada vez mais exigente em qualidade, a hidroponia se apresenta como uma técnica bastante promissora, devido as suas principais vantagens: controle no uso de nutrientes; antecipação da colheita; homogeneidade de oferta e qualidade dos produtos durant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 5 publications
(1 reference statement)
3
11
1
12
Order By: Relevance
“…the leaf epidermis near the guard cells of stomata. Similar results to those found for coffee in this work were found by Luz et al (2006) for lettuce. The authors, however, found no significant effect on the content of Si in the roots.…”
Section: Resultssupporting
confidence: 92%
“…the leaf epidermis near the guard cells of stomata. Similar results to those found for coffee in this work were found by Luz et al (2006) for lettuce. The authors, however, found no significant effect on the content of Si in the roots.…”
Section: Resultssupporting
confidence: 92%
“…In comparison to the literature, the mean CD observed in the present study, which was equal to 29.97 cm (Table 2), is higher than that cited by Luz et al (2006), who worked with the hydroponic system using the solution of Furlani and found means of 28.02 cm. However, this difference can be associated with the high temperatures recorded in the cultivation environment, because these authors obtained a mean higher than that of the present study.…”
Section: Resultscontrasting
confidence: 91%
“…The concentrations of 0.55 and 0.83 g silicon pot -1 resulted in a higher silicon content in the root compared to the other treatments, and the 0.28 g silicon pot -1 treatment showed silicon content higher than observed in the control. The presence of silicon in the control can be explained by the abundance of silicon in nature, where it is ubiquitous and is found even in water (Luz et al, 2006).…”
Section: Silicon Concentrationmentioning
confidence: 99%